2016
DOI: 10.1111/pcmr.12531
|View full text |Cite
|
Sign up to set email alerts
|

Two light‐activated neuroendocrine circuits arising in the eye trigger physiological and morphological pigmentation

Abstract: Two biological processes regulate light-induced skin colour change. A fast 'physiological pigmentation change' (i.e. circadian variations or camouflage) involves alterations in the distribution of pigment containing granules in the cytoplasm of chromatophores, while a slower 'morphological pigmentation change' (i.e. seasonal variations) entails changes in the number of pigment cells or pigment type. Although linked processes, the neuroendocrine coordination triggering each response remains largely obscure. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…To understand whether in older animals the eye plays any role in the skin pigmentation response to ambient darkness, we measured skin pigmentation for larvae in which the eye or the pineal complex was surgically removed. As we showed previously (Bertolesi, Hehr, et al., ), the pineal complex did not appear to be involved in the darkening of the skin of stage 42 dark‐reared embryos, while the eye is critical in the process (Figure a,b). Embryos missing their pineal complex were still darker when reared in the dark versus the light, whereas eye removal blocked the ability of light to lighten the embryo, such that the pigment index of stage 42 embryos missing their eyes was indistinguishable from that of embryos reared under dark conditions (Figure a,b; control light versus control dark and no eye‐light).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…To understand whether in older animals the eye plays any role in the skin pigmentation response to ambient darkness, we measured skin pigmentation for larvae in which the eye or the pineal complex was surgically removed. As we showed previously (Bertolesi, Hehr, et al., ), the pineal complex did not appear to be involved in the darkening of the skin of stage 42 dark‐reared embryos, while the eye is critical in the process (Figure a,b). Embryos missing their pineal complex were still darker when reared in the dark versus the light, whereas eye removal blocked the ability of light to lighten the embryo, such that the pigment index of stage 42 embryos missing their eyes was indistinguishable from that of embryos reared under dark conditions (Figure a,b; control light versus control dark and no eye‐light).…”
Section: Resultssupporting
confidence: 73%
“…Next, we asked whether stage 47/8 melanophores showed similar responses to exogenous melatonin and α‐MSH as we reported previously for stage 42 embryos (Bertolesi, Hehr, Munn, & McFarlane, ; Bertolesi, Vazhappilly, et al., ). Stage 39 embryos and 47 larvae were raised in light with a white background or in the dark for 24 hr, before adding melatonin (10 n m ) or α‐MSH (1 μ m ) (Figure a,b).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Both PCC and MCC may be involved in melanin-based pigmentation. Generally speaking, PCC is more active and rapid than MCC in response to environmental brightness in fish and amphibians [ 1 ], and in most studied cases, activation of MCC is always accompanied by PCC, as factors inducing MCC can also activate PCC [ 53 ]. However, in O. rhodostigmatus tadpoles, genes involved in MCC, or more exactly melanogenesis and melanocyte proliferating, increased with skin darkening, while those involved in PCC did not (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, pupillary constriction (Chen et al, 2011;Gooley, Lu, Fischer, & Saper, 2003) and sleep induction Lupi et al, 2008) also depend on light activation of ipRGCs. It was only melanopsin expression by skin melanophores of LEI organisms that suggested a function in regulating pigmentation (Isoldi et al, 2005;Rollag et al, 2000), until we showed recently that retinal melanopsin in the eye indirectly regulates pigmentation through activation of a neuroendocrine circuit (Bertolesi, Hehr, & Mcfarlane, 2015;Bertolesi, Hehr, Munn, & McFarlane, 2016;Bertolesi, Song, Atkinson-Leadbeater, Yang, & McFarlane, 2017;Bertolesi, Vazhappilly, Hehr, & Mcfarlane, 2016). Indeed, ipRGCs regulate the secretion of melatonin (Lucas, Freedman, Muñoz, Garcia-Fernández, & Foster, 1999;Lupi et al, 2008;Sekaran et al, 2005) and α-MSH (Bertolesi et al, 2015), which modulate skin pigmentation of LEI and LPI organisms (Jenks, van Overbeeke, & McStay, 1977;Slominski, Tobin, Zmijewski, Wortsman, & Paus, 2008).…”
Section: Seeing the Light: Melanopsin Expression And The Evolutionamentioning
confidence: 99%